The search for appropriate dispute resolution mechanisms to resolve aboriginal land claims : empowerment and recognition - Montminy, Joëlle (Allard Research Commons, 2010)
Different dispute resolution mechanisms, including treaties, litigation, negotiation and, to a lesser extent, mediation and arbitration, have been employed to resolve land disputes in Canada over the centuries. Since 1973, the federal government has unilaterally developed and reviewed land claims policies which favour negotiation to resolve land claims between governments and First Nations, Further, two regional institutions were created in Ontario and British Columbia to facilitate the resolution of these complex claims. Various processes have also been used to resolve similar claims in New Zealand and Australia. The problems associated with the present land claims processes in Canada have been discussed for more than twenty years. The purpose of this thesis is to analyze the appropriateness of the various dispute resolution processes which are, or could be, employed to resolve the land question in Canada. The search for dispute resolution mechanisms suitable to resolve land claims is undertaken in light of the two basic characteristics of the relationship of the parties to these disputes: the cultural differences, and the imbalance of power between the parties. The first chapter of my thesis examines the history of land claims policies and processes in Canada, discusses the historical relationship between Aboriginal peoples and governments, and explores the main assumptions, premises, values and beliefs held by the parties involved in Aboriginal disputes, and the dynamics of their relationship. The following three chapters discuss specific dispute resolution processes which have been employed to resolve the land question in Canada. At the end of each of these chapters, suggestions are made to improve these various processes. Chapter Two analyzes the advantages and disadvantages of litigation in the context of Aboriginal land cases. Chapter Three examines the process of negotiation, with a focus on the federal government’s policies on land claims. Chapter Four discusses the processes of mediation and arbitration, and considers the appropriateness of these mechanisms to resolve land claims in Canada. Chapter Five provides a comparative look at three institutions which have been created to resolve Aboriginal claims in New Zealand, Australia and Canada: the Waitangi Tribunal of New Zealand; the National Native Title Tribunal of Australia; and the British Columbia Treaty Commission. Finally, Chapter Six identifies the essential elements which must be present for dispute resolution mechanisms to be successful in the Aboriginal land claims context and integrates these basic principles into a general model of dispute resolution for Canada. In the course of my research, I have examined literature dealing with alternative dispute resolution (ADR), the resolution of Aboriginal claims, and on Aboriginal law generally. Throughout this thesis, I have used different methods of research and analysis. The critical approach is used to question the self-professed legitimacy and fairness of some dispute resolution processes, as well as to examine the theoretical underpinnings of various processes for cultural biases. The comparative method is helpful in analyzing different institutions that have been created in Australia, New Zealand and British Columbia to resolve Aboriginal claims. Finally, considering that the field of dispute resolution is informed by a wide variety of disciplines, the interdisciplinary approach is used to present different propositions concerning which dispute resolution mechanisms are the most appropriate to resolve Aboriginal land claims based on anthropological, historical, sociological and political variables. One of the difficulties in trying to find appropriate dispute resolution mechanisms to deal with Aboriginal land claims is to accommodate the diversity of the approximately 633 First Nations in Canada. Another difficulty relates to the fact that most of the ADR literature rarely addresses the issue of cultural differences. This thesis concludes that the various dispute resolution mechanisms studied have both advantages and disadvantages for resolving the land question in Canada. I suggest that each mechanism has a role to play in the overall process of resolving Aboriginal land claims as long as it accommodates the cultural diversity and ensures that all concerned have a voice in designing the process(es) employed to resolve land disputes. This thesis also recommends the creation of an independent land claims body which would provide the benefits of third-party intervention while avoiding the deficiencies of the present judicial system. Objectives would be to reduce costs, expedite procedures, permit flexibility in the handling of polycentric problems, maximize the involvement of the parties in the process and outcome, and facilitate the production of a settlement which contributes to future harmonious relationships between Aboriginal and non-Aboriginal society. The most important element remains that discussions about possible changes to the existing processes should occur between governments in partnership with the First Nations of Canada, and in consultation with non-Aboriginal interests.